EFEKTIVITAS PELAKSANAAN PROGRAM BANTUAN DANA ( BLOCK GRAND)/ALOKASI DESA DI KELURAHAN AIR TIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Arza Rahliadi; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Organization is a means or instrument achieving  goals . Therefore, the organization is said to be a container or vehicle , the activities of people who work together to achieve goals . In container activity that everyone had clear goals and objectives to be achieved . Furthermore, the organization is the Village and Community Institutions that exist in urban districts Air Tiris Kampar Kampar district is one element of governance at the village , which has a role to implement the program block grant / allocation of rural / urban village development in order to realize the physical and nonphysical effective . Allocation Fund , hereinafter referred to as ADD village are funds allocated by local government to the village , which is sourced from the financial balance and regional distribution center for each village fair and proportionate manner in which the principles of the use and management is also listed therein . There are several objectives and targets to be achieved from assistance Assistance Fund ( block grant ) allocation village / kelurahanini , diantaranyaadalah : ( 1 ) . ability to empower rural communities in accordance with the characteristics of its people , especially its ability in leading sectors that can boost rural incomes / village ; ( 2 ) . improve the implementation of the Government in  the village government services , community development and in accordance with the authority ; ( 3 ) . enhance the ability of an association of villages in the planning and implementation of development control in accordance with the potential of participatory village ; ( 4 ) . improve the distribution of income , employment and business opportunities for rural communities ; ( 5 ) . encourage self-help mutual aid society . The purpose of this study is based on research problems is to determine whether sufficient effective implementation of the Programme Aid Fund ( block grant ) allocation of rural / urban districts dikelurahan Air Tiris Kampar Kampar district and anything what factors that influence the effectiveness of the program pelanksanaan bantauan the  block grant .  The concept of the theory is the theory of implementation that is used in Nugroho Grindle (2003 : 174 ) said about the success of policy implementation , namely : after the policy is transformed , then the policy implementation done . Its success is determined by the degree Implementabiliti of the policy. In this case viewed from the implementation of block grant program proficiency level in accordance with the goals and objectives that have been set . With descriptive qualitative research methods , and research sites in urban districts Air Tiris Kampar Kampar district is the village chief informant and devices ,  Kasi  Empowerment  Village Community / Village in the district of Kampar , Chairman of the LPM , and Chairman of the BPD , as well as several community leaders .  From the results, it can be concluded Jom FISIP Volume 1 No. 2 – Oktober 2014  2that the implementation of the block grant program grat / allocation in the village of village water districts Tiris Kampar Kampar district has not been effective in accordance with the goals and objectives of the block grant program itself. As in katakana Grindle in Nugroho ( 2003) after the policy is transformed , then the policy implementation done . Its success is determined by the degree Implementabiliti of the policy. However implemetabiliti of the block grant program has not been run in accordance with the goals and objectives that have been set.Kata Kunci:  Efektifitas, Pelaksanaan, Program Bantuan Dana (block grant)Alokasi Desa